2020
DOI: 10.1111/eip.13016
|View full text |Cite
|
Sign up to set email alerts
|

A routine outcome measure for youth mental health: Clinically interpreting MyLifeTracker

Abstract: Aim: MyLifeTracker is a session-by-session mental health outcome measure for young people aged 12 to 25 years. The aim of this study was to determine clinically significant change indexes for this measure that would identify developmentally appropriate thresholds. The study also aimed to determine expected change trajectories to enable clinicians to compare a client's progress against average rates of change. Methods: Participants comprised young people aged 12 to 25 years from both a clinical and a community … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
17
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 12 publications
(18 citation statements)
references
References 59 publications
1
17
0
Order By: Relevance
“…The implementation of MLT as a part of the electronic data collection system used across headspace services is highly progressive. However, it was initially implemented for monitoring and evaluation purposes, rather than for clinical utility, which has only been more recently supported (Kwan et al, 2018;Kwan & Rickwood, 2020;Rickwood et al, 2018;Rickwood et al, 2015). Therefore, these results are unsurprising but reinforce the need for the organisation to focus on these neutral or negative perceptions of championing, training, and clinical support to support MLT use.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The implementation of MLT as a part of the electronic data collection system used across headspace services is highly progressive. However, it was initially implemented for monitoring and evaluation purposes, rather than for clinical utility, which has only been more recently supported (Kwan et al, 2018;Kwan & Rickwood, 2020;Rickwood et al, 2018;Rickwood et al, 2015). Therefore, these results are unsurprising but reinforce the need for the organisation to focus on these neutral or negative perceptions of championing, training, and clinical support to support MLT use.…”
Section: Discussionmentioning
confidence: 99%
“…Importantly, benchmarks have recently been created for MLT in the form of clinically significant change indexes by age group and gender and expected change trajectories established by baseline MLT scores (Kwan & Rickwood, 2020). These benchmarks are yet to be incorporated within the headspace electronic data collection system, where they will provide additional clinical information for clinicians and clients.…”
Section: Practical Implicationsmentioning
confidence: 99%
See 1 more Smart Citation
“…To avoid the risk of it becoming a purely bureaucratic exercise, outcome measurement should be meaningful to clinicians, young people, and families and carers [ 6 , 45 , 49 52 ]. The dearth of clinically meaningful outcome measures designed for young people has been previously highlighted [ 53 ], but such measures are being developed [ 54 , 55 ]. It has also been advocated that using idiographic outcome measures (e.g.…”
Section: Discussionmentioning
confidence: 99%
“…This suggests that either female and younger participants had differential reporting behaviours, or improvements in subjective cognitive function are harder to achieve in these groups. Partial support for the latter hypothesis comes from a large Australian cohort study of young people, which monitored subjective quality of life using MyLifeTracker and found that younger male adolescents aged 12 to 14 years needed to reach higher scores to achieve clinically significant change compared to those aged 15–25 years (Kwan & Rickwood, 2020). Hence, while attention to cognition concerns should be paid to all young people receiving mental health treatment, our data suggest females and younger adolescents may be especially affected.…”
Section: Discussionmentioning
confidence: 99%